Association of Weight With Sociometric Status in Classrooms of Taiwanese Adolescents. (June 2020) - Lu, Hsin-Hui; Chen, Duan-Rung
This study examined the association between adolescents' obesity and sociometric status among their peers across 1 year. The participants were 2, 528 junior high school students from Taiwan (mean age = 13.31 years). The negative associations discovered between obesity and sociometric status were both concurrent and cumulative. Moreover, the adolescents who changed from nonobese to obese were more likely to have lower social acceptance and be isolated in their classrooms. These findings inform concerns regarding the sociometric status of adolescents who are (or are becoming) obese.